The characteristics of Indonesian multicultural movie audiences in post-1998: a study of the Yogyakarta movie community - Sukmono, Filosa Gita; Bajari, Atwar; Maryani, Eni; Agustin, Herlina (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study aims to open further studies of the characteristics of Indonesian movie audiences towards national multicultural movies after 1998 or the fall of new order regime. It is motivated by an assumption that the shift in the system and atmosphere of democracy in Indonesia after 1998 affects Indonesian audiences' understanding of multicultural movies, which was perceived as a sensitive issue beforehand. Additionally, this study aims to grasp the Indonesian knowledge of the idea of multiculturalism. The study picked Yogyakarta movie communities as the research participant and applied focus group discussion as a method for data collection. Yogyakarta itself was preferred since it is one of the regions in Indonesia with distinctive movie literacy. The research shows three main characteristics of Indonesian audiences’ post 1998, namely euphoric, open, and limited. Euphoric means local audiences are beginning to favor multicultural themes in their watching lists; open means that viewers are starting to accept various multicultural issues, primarily related to identities, and, finally, limited means audiences’ references are mostly determined by theater schedules and insignificantly by alternative spaces. Although scope's intensification is necessary, the research is instructive enough to point out the unique changes in the culture of watching multicultural movies after 1998 in Indonesia.